A new view on old problems in paediatric anaesthesia: premedication, postoperative agitation and dosing. Issue 3 (11th June 2023) - Jöhr, Martin
Abstract : Purpose of review: The aim of this review is to discuss recent developments in paediatric anaesthesia, which have evolved in an undulating fashion. Recent findings: The role and efficacy of pharmacological premedication is reevaluated. The anxiolytic and sedative properties of midazolam and α2 -agonists have now been defined more precisely. Both classes of drugs have their unique profile, and there is no reason to condemn one or the other. Midazolam is an excellent anxiolytic, whereas dexmedetomidine is superior in the postoperative period and for sedation during diagnostic imaging. A total intravenous technique with propofol is often considered to be the standard for the prevention of emergence agitation; but alternatives do exist, such as a co-medication with dexmedetomidine or opioids. In clinical reality, a multimodal approach may often be advisable. The theoretical basis for propofol dosing has recently been adapted. In contrast to previous beliefs, the context-sensitive half-life of propofol seems to be quite short beyond the first year of life. Summary: Midazolam and dexmedetomidine are not interchangeable; each compound has its pros and cons. As an anxiolytic drug, midazolam indisputably deserves its place, whereas dexmedetomidine is a better sedative and particularly beneficial in the postoperative period. New data will allow more precise age-adapted dosing of propofol.